Impact of Cumulative Smoking Exposure on Subclinical Degenerative Aortic Valve Disease in Apparently Healthy Male Workers. (August 2019) - Yamaura, Yasuko; Watanabe, Nozomi; Shimaya, Maki; Tomita, Yasuhiko; Fukaya, Takashi; Yoshida, Kiyoshi
Abstract : Background: Little is known regarding the impact of cumulative smoking exposure and smoking cessation on subclinical degenerative aortic valve (DAV) disease. Methods: We examined associations of smoking status, cigarette-years of smoking, and years since quitting smoking with subclinical DAV disease defined by echocardiography. Results: Of 756 apparently healthy male workers, 154 had DAV including 63 with DAV with ≥2 leaflets calcification (DAV ≥2 cal). Compared with never smokers, ever smokers had higher risk of DAV and DAV ≥2 cal; odds ratios (95% CI) were 2.883 (1.800–4.618) ( p <0.001) and 5.281 (2.297–12.138) ( p <0.001), respectively. Both current and former smokers had dose-dependent relationships of cigarette-years on DAV and DAV ≥2 cal ( P for trend, <0.001 for both DAV, in both smokers). In current smokers with >400–⩽800 and with >800 cigarette-years, odds ratios (95%CIs) were 3.201 (1.690–6.063) ( p <0.001) and 5.326 (2.800–10.053) ( p <0.001) for DAV, 7.460 (2.828–19.680) ( p <0.001) and 8.397 (3.146–22.414) ( p <0.001) for DAV ≥2 cal, respectively. In former smokers with >800 cigarette-years, odds ratios (95%CI) were 3.780 (1.970–7.254) ( p <0.001) for DAV, 10.035 (3.801–26.496) ( p <0.001) for DAV ≥2 cal. Compared with current smokers, former smokers with quitting smoking >10 years had significantly lower risk of DAV and DAV ≥2 cal. Conclusions: In apparently healthy male workers, DAV disease was strongly associated with smoking. Cumulative smoking exposure was associated with dose-dependent relationship on subclinical DAV disease both in current smokers and former smokers.